The Effect of Work Life Balance and Job Satisfaction on Employee Performance at PT. Pegadaian Cabang Kota Palopo - Nanna; Haedar; Adil Basir (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the effect of work life balance and job satisfaction on employee performance at PT. Pegadaian Branch of Palopo City. This type of research is quantitative research by distributing questionnaires online to respondents with a total of 32 people. By using the saturated sampling method. the data used in this study, primary data was taken directly from respondents using a questionnaire. This method uses the SPSS version 22 program. The results of the study based on the results of the t analysis showthatbalance between work lifeand satisfactionin work has an impactpositive and significant towardsperformanceemployeeat PT. Pegadaian Branch of Palopo City. Judging from the determination of R square of 0.954 which means 95.4% can be explained by other variables included in this study. The results obtained are F count 320.270 > F table 3.32. With this, the hypothesis that states there is an influence between the independent variables Work Life Balance (X1) and Job Satisfaction (X2) simultaneously on the dependent variable Employee Performance (Y) can be accepted